A correlation analysis of Lee’s grade CKD stage and hypertension in IgA nephropathy - LIAO Ying; HE Yong-cheng; HU Hao-fei; QI Dong-li (Linchuang shenzangbing zazhi)
Objective To analyze the correlation of Lee’s grade CKD stage and hypertension in IgA nephropathy in order to provide the basis for guiding diagnosis and treatment of primary IgA nephropathy.Methods A total of 430 patients with primary IgA nephropathy diagnosed by renal biopsy in Shenzhen 2nd People’s Hospital were enrolled as the research objects.We analyzed their clinical data,including sex,age,weight,blood pressure,serum albumin,creatinine,uric acid,blood lipids(total cholesterol,triglyceride,low density lipoprotein cholesterol,high density lipoprotein cholesterol),24-h urinary protein and renal pathology Lee’s grade.The glomerular filtration rate was estimated by serum creatinine levels.These patients were divided into CKD stage 1-5 according to the estimated glomerular filtration rate.At the same time,these patients were divided into hypertension group(including hypertension grade 1,2 and 3) and non-hypertension group according to the level of blood pressure.The correlation between hypertension and the clinical data,renal pathology Lee’s grade,CKD stage was analyzed.Results Among 430 IgA nephropathy patients,the male:female ratio was1.05:1,the age was 13 to 72 years old(mean 34.5 ± 9.4 years),and incidence peak age was 21-30 years old.Age was older and weight was heavier in hypertension group than in non-hypertension group(P<0.05 for both).The prevalence of hypertension in these group data was 46.7%.In hypertension group,there were 42 patients with hypertension grade 1(9.8%),57 patients with hypertension grade 2(13.2%),and 102 patients with hypertension grade 3(23.7%),respectively.The age was older,body weight was heavier,and 24-h urinary protein,serum creatinine,uric acid,total cholesterol,triglyceride and low density lipoprotein cholesterol were higher,and the serum high density lipoprotein cholesterol was lower in hypertension group than in non-hypertension group(P<0.05 for all).There were 66,63 and 44 cases of renal pathology Lee’s grade,Ⅳ and Ⅴ,respectively in hypertension group.Spearman correlation analysis showed that hypertension was correlated with renal pathology Lee’s grade(r=0.394,P=0.0000).There were 60,36 and 11 cases of CKD stage 3-5 respectively in hypertension group.Spearman correlation analysis showed that hypertension was correlated with CKD stage(r=0.477,P=0.0000).Multiple factors Logistic regression analysis showed that serum creatinine,Lee’s grade and CKD stage were correlated with IgA nephropathy with hypertension.Conclusions The prevalence of IgA nephropathy with hypertension was higher,and its CKD stage and renal pathology Lee’s grade were more severe correspondingly.So we should strengthen the control of blood pressure to delay the progress of renal dysfunction.